EMOTIONAL ASPECTS INVOLVING OBESITY: A GROUP PSYCHOTHERAPEUTIC APPROACH (CIPEEX, 2026)
Obesity is a major public health challenge, linked to chronic diseases such as diabetes and hypertension, in addition to having emotional and psychosocial impacts (Brazil, 2023). Given this, it is essential to adopt an approach that combines physical and emotional aspects, with an emphasis on group psychotherapy. This study investigates the emotional and social factors in the care of overweight people, evaluating group therapy as a strategy to support change. The methodology involved observing group meetings and interviews, allowing for a better understanding of the interactions between participants and therapists. The analysis is based on Pichon-Rivière's (1988) bond theory and Yalom (2006), focusing on instilling hope and clinical discussions among therapists. The results reveal benefits such as belonging, empathy, exchange of experiences, and greater adherence to treatment.
Keywords: Morbid obesity; bariatric surgery; terapia; HOPE